Terraforming Tech City: Place branding and spatial imaginaries in inner East London - Max Nathan; Emma Vandore; Georgina Voss (University of Birmingham, Birmingham Business School, 2016)
This paper performs a mixed-methods analysis of place-branding strategies developed in the 'Tech City' cluster initiative in Inner East London, drawing on ethnographic material, semi-structured interviews and visual content. Using Jessop's concept of the spatial imaginary, we explore key foundational geographies, trace the emergence of the 'Silicon Roundabout' and Tech City concepts between 2008 and 2014, then discuss Tech City's governance and progress, highlighting both day-to-day challenges and more basic tensions. We contrast this experience with that of 'Here East', a new regeneration space across the city in the Olympic Park.
Keywords: 330; cities; clusters; spatial imaginaries; place branding; economic development; urban governance